Nutrient Utilization in some Tropical Forest Tree Seedlings - , Lalman; Misra, A. (Indian Forester, 1985)
The conceatration of nitrogen, phosphorus, potassium, Calcium aad sodium has been estimated in one year seedling of Dalbergia sissoo Roxb., Tamarindus indica Linn., Diospyros melanoxylon Roxb., Terminalia arjuna Bedd and Tectona grandis Linn. The percentage of N, P, K. Ca and Na was highest in leaves followed by decrease in stem and root respectively in seedlings of all species. The mineral composition of leaves in each species increased steadily with advance of age of seedlings till 8-9 months at the time yellowing of leaves. After this remarkable decrease in N, P, K content was noticed. However, a little decrease in Ca and Na content of leaves was also noticed. There was continuous and steady increase of N, P and K content of stem and root of seedlings of each species. But the Ca and Na content increased for 8 to 10 months of seedlings age after which narrow downfall was observed. The concentration of sodium in leaves was relatively, higher than P, K and Ca in D. sissoo, T. indica, T. arjuna and T. grandis. It was higher than N also in D. melanoxylon. The N, P, K, Ca and Na have been analysed from fresh litter and found to be very closure but relatively lower than those of mature leaves.